Interaksi Antara Syariat dan Kearifan Lokal Islam Jawa dalam Perspektif Sosiologis - Afifi Nur Laila Nur Hasanah , Siti; Rahmah, Maulidiana (Postgraduate Studies UIN Sunan Ampel Surabaya, 2024)
This article explores the combination of Islamic law and local wisdom in Java in a social and cultural context. The da'wah approach used by the Walisongo, Islamic preaching scholars in Java, emphasizes harmonization between Islamic teachings and local traditions. Through art, culture and social structures, Islam was well accepted by the Javanese people who previously adhered to Hindu-Buddhist religion in the 15th and 16th centuries. This phenomenon creates a unique identity known as Javanese Islam, which is inclusive and moderate. Although most of the Islamization process took place in harmony, this article also examines the tension between traditionalist Islamic groups who support syncretism and modernist groups who encourage a purer application of Islam. With a sociological approach, this article explores how Islam was adapted into the lives of Javanese people and how this acculturation formed a new social order where religion is not only understood as a belief system, but also as a social force that interacts with local culture.